2023
DOI: 10.3390/pathogens12101187
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Transmission of Theileria orientalis in Australasia

Biniam T. Lakew,
Steve Eastwood,
Stephen W. Walkden-Brown

Abstract: Oriental theileriosis, a disease primarily impacting cattle is caused by an apicomplexan hemoprotozoan parasite, Theileria orientalis. It has now become established in the Australasia region. The organism was long considered a benign cause of persistent infections; however, an increase in clinical outbreaks since 2006 in the eastern Australian states and New Zealand was associated with the identification of the pathogenic Ikeda (Type 2) and Chitose (Type 1) genotypes. Unlike the pathogenic T. parva and T. annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Theileria orientalis ( T. orientalis ) is widely distributed and causes theileriosis, a condition in which the pathogen invades and destroys red blood cells of the host after entering via a tick bite [ 1 , 2 ], and T. orientalis is mainly transmitted by the Hemaphysalis longicornis ( H. longicornis ) vector [ 3 ]. T. orientalis is transmitted throughout a tick’s lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Theileria orientalis ( T. orientalis ) is widely distributed and causes theileriosis, a condition in which the pathogen invades and destroys red blood cells of the host after entering via a tick bite [ 1 , 2 ], and T. orientalis is mainly transmitted by the Hemaphysalis longicornis ( H. longicornis ) vector [ 3 ]. T. orientalis is transmitted throughout a tick’s lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Theileria (T.) orientalis, a tick-borne haemoparasite of cattle, is an important cause of non-transforming theileriosis in Australasia, southeast Asia, and the United States [1][2][3]. Clinically affected cattle often display symptoms such as anaemia, hypoxia, weakness, and increased cardio-pulmonary rates [4,5].…”
mentioning
confidence: 99%
“…The taxonomy of T. orientalis has been a subject of debate, with three previously proposed species: T. buffeli (Australia), T. sergenti (Japan), and T. orientalis (Europe and elsewhere) [6]. However, recent evidence from PCRdirected sequencing and phylogenetic analyses of major piroplasm surface protein (MPSP) sequences has confirmed that they all belong to the same T. orientalis species, comprising 11 distinct allelic types, including the Ikeda type typically associated with clinical disease [1][2][3].…”
mentioning
confidence: 99%
See 1 more Smart Citation